P365 Microbial risk factors for acquisition of symptomatic Bacterial Vaginosis (BV). (14th July 2019) - Beamer, May; Meyn, Leslie; Petrina, Melinda; Cosentino, Lisa; Avolia, Hilary; Austin, Michele; Demarco, Allison; Gould, Victoria; Hillier, Sharon
Abstract : Background: Vaginal dysbiosis is common among women of reproductive age but many women having vaginal dysbiosis do not develop symptomatic BV requiring treatment. Our objective was to identify microbiota using quantitative PCR (qPCR) which were associated with acquisition of symptomatic BV. Methods: In this secondary analysis of a vaccine trial, 440 healthy asymptomatic sexually active women aged 18–40 had vaginal swabs collected at baseline and returned at 1, 2 and 4 months. Eleven vaginal microbes at baseline were identified using qPCR (five species of Lactobacillus (crispatus, vaginalis, jensenii, gasseri, iners ), three species of Prevotella (bivia, timonensis, amnii ), Atopobium vaginae (AVAG), Gardnerella vaginalis (GVAG) and Megasphaera phylotype I (MEGA). Time to first acquisition of symptomatic BV was based on self-report of antibiotic treatment for BV. Cox proportional hazards models were used to evaluate the association of microbiota with BV acquisition. Results: Thirty-five women developed symptomatic BV over 130.7 person-years (PY) of follow-up for an overall rate of 27/100PY. Women who acquired BV had a lower baseline prevalence of L. crispatus than those who did not (31.4% vs 57.8%; P =0.012), and a higher prevalence and log concentration of GVAG (97.1% vs 76.0%), AVAG (77.1% vs 43.7%), MEGA (65.7% vs 23.2%), P. timonensis (80.0% vs 61.7%), and P. amnii (51.4% vs 20.5%), ( P ≤0.001). In multivariable analyses, women who had GVAG, AVAG, and MEGA at baseline had a significantly higher BV acquisition rate (74/100 PY, hazard ratio=21.2; 95% confidence interval: 2.8–158.8) compared to women who had none of these microorganisms (rate=4/100 PY). Women who had only one (BV rate=16/100 PY) or two (BV rate=14/100 PY) of the three microbes detected at baseline were not more likely to acquire BV (P≥0.14). Conclusion: Although many individual bacteria contribute to the dysbiotic communities associated with BV, the combination of GVAG, AVAG, and MEGA rather than presence of lactobacilli predicts symptomatic BV. Disclosure: No significant relationships.